Peningkatan Kemampuan Investigasi Matematika Melalui Pemberian Proyek Matematika Pada Siswa Kelas XI - Aisyah Amin; Nurdin Arsyad; Ilham Minggi (Universitas Islam Negeri (UIN) Mataram, 2015)
This study is a classroom action research wihch aims at improving investigation ability of mathematics on function derivation and describing the process of mathematics learning by providing Mathematics Project. The subject of the study was 40 students grade XI IPA 1 SMAN 2 Watampone of academic year 2011/2012. The improvement of mathematics investigation ability was measured by investigation ability indicators, namely (1) problem identification, (2) organization and collection of information/facts/Mathematics symbols, (3) building and implementation of planning and problem solving, (4) drawing conclution, (5) interpretation of the result of investigation, and (6) communicating the result of investigation. The study was conducted in two cycles by following the stages of classroom action research on each of the cycle consist of (1) the planning, explaining of the preparation based on the result of pre-action wich resulted on low investigation ability, (2) the action, the implementation from all of the planning of action constructed on the first stage, (3) the observation, observation during the action wich obtained quantitative data and qualitative data, and (4) the reflection, the stage to study and process the data obtained during the observation. The instrument of study used observation sheet and test of investigation ability of mathematics. The observation sheet was used to evaluate the implementation of learning process by giving Mathematics project assignment. Whereas, the test of investigation ability of Mathematics was used to evaluate the improvement of students‟ investigation ability. The results obtained after giving the project assignment are (1) on cycle I, the mean score of students‟ investigation ability after the learning is 57,05; (2) on cycle II, the result is 80,58. The observation sheet reveals that students have improvement on the activeness and ability in conducting investigation toward the project assignment proven by the achievement of indicators of investigation ability wich improved on each of cycle. The conclution based on the result of observation and test of investigation ability is there is adequately significant improvement ofmathematics investigation ability on each of the cycle.